The Evolution of Islamic Educational Thought in Preparing for the Era of the Fourth Industrial Revolution and Society 5.0 - Silvia Marlina; Rizki Eka Putra; Budi Budi; Yuharniza Yuharniza; Moh. Arief Hidayat; Saifullah Saifullah; Riki Saputra (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
The advent of the Fourth Industrial Revolution and the emergence of Society 5.0 have engendered profound transformations within contemporary educational paradigms, compelling Islamic education to recalibrate its orientation in response to rapid technological advancements while steadfastly preserving its spiritual substratum. This study is undertaken to critically examine the intellectual foundations of Islamic education in confronting such multifaceted challenges and to formulate strategic directions for its progressive development. Employing a qualitative library research design, the study draws upon a corpus of recent scholarly works, encompassing academic monographs and peer-reviewed journal articles pertinent to the discourse. The findings disclose that Islamic education necessitates a paradigmatic reconfiguration through the epistemic integration of religious and secular sciences, the pedagogical transmutation via technology-enhanced learning modalities, and the fortification of moral and spiritual character. Such integrative and transformative measures are deemed indispensable in mitigating the adverse ramifications of technological proliferation. In conclusion, Islamic education retains substantial potential to remain contextually germane and to cultivate a generation endowed with intellectual acumen alongside robust ethical and spiritual integrity in the contemporary epoch.